Analisis Kinerja Biaya dan Waktu dengan Metoda Earned Value serta Percepatan Sisa Pekerjaan Proyek Jembatan dengan Metoda Crashing - Irfan Achmad Taufik; Anton Soekiman; Chandra Afriade Siregar (Jurnal Konstruksi, 2025)
This study analyzes the cost and time performance of the Sequoia Hills Bridge project in Bogor City using the Earned Value and Crashing methods. The EVM analysis results in week 8 show that time performance is slightly behind schedule (SV -1.17%) but cost performance is more economical (CV 0.17%). Overall, the project shows efficiency with an SPI of 1.30 and a CPI of 1.02, projecting completion 35 days ahead of schedule (EAS 175 days) and cost savings of IDR 40.5 million from the RAB. To meet the project owner's request for acceleration, a Crashing simulation was conducted on the remaining work with various overtime scenarios. The best scenario is adding 4 hours of overtime to critical work, resulting in an optimal duration of 165 days, which is faster than the initial remaining duration of 171 days. This study provides a reference for contractors in monitoring project performance and determining efficient and economical acceleration strategies.